Representing the Ukrainian Migration Experience: From a Cultural Monologue Towards Interculturality - Kupidura, Ryszard (Porównania, 2023)
The text is devoted to literary, theatrical and film representations of the Ukrainian migration experience in Poland. The author notes that current artistic strategies, contrary to the intentions of Polish writers/artists, often reinforce stereotyping patterns of reception of the Other and unconsciously postulate an essentialist project of portraying a “real Ukrainian woman/man.” On the other hand, Ukrainian voices are increasingly heard in Polish space, which provides an opportunity not only to work through painful traumas from the past, but, due to the constant presence of Ukrainian co-residents, also to develop competences in recognizing mutual cultural codes, which in turn creates an opportunity to avoid generating new traumas in the future. The author devotes separate attention to the multidimensional Ukrainian-Ukrainian dialogue taking place in recent years in the territory of Poland, in other words, to the relations between the Ukrainian minority and Ukrainian migrants.